A Systematic Review: Down-flow Hanging Sponge Application for Wastewater Treatment Technology - Kyky Fadhila Cindya Putri; Aulia Ulfah Farahdiba; Munawar Ali (Nusantara Science and Technology Proceedings)
To reduce waste water pollution in Indonesia, it is necessary to conduct renewable research. One of the studies designed as an energy-efficient and easy-to-maintain alternative is the downflow hanging sponge (DHS). DHS has been studied in various countries and is being developed. from some of these studies will be summarized in this paper about the mechanism of the dhs process, the microorganisms formed in dhs, and the factors that affect the performance of dhs.